Neuroimaging in drug resistant epilepsy - Sachdev, Namrita; Gupta, Shivani; Prasad, Akhila (International Journal of Research in Medical Sciences, 2018)
Background: Epilepsy is a common serious neurological condition and 30 to 40 % of people with epilepsy have seizures that are not controlled by medication. Patients are considered to have drug resistant epilepsy if disabling seizures continue despite appropriate trials of two anti-epileptic drugs. Most lesions causing drug resistant epilepsy can be detected by 3T MR Imaging using dedicated epilepsy protocol which is crucial for diagnostic and subsequent therapeutic planning with benefit from surgery. We present a review of the major abnormalities related to drug resistant epilepsy, highlighting the key findings of 3 T MRI. Methods: A Cross-sectional Observational study was done in 30 patients. Patients less than 60 yrs of age of either sex, diagnosed with DRE as per ILAE criteria, were included in the study. 3T MRI was performed using dedicated epilepsy protocol, with additional 3D imaging for manual hippocampal volumetric evaluation. Results: About 77% cases showed an MRI abnormality on visual assessment, with additional 16% cases showing abnormal MRI findings on manual hippocampal volumetry. Nearly 50% of the abnormal MRI cases showed Mesial Temporal Sclerosis, followed by neoplasms as etiology of DRE. Conclusions: MR imaging has significantly improved detection of pathologies related to epilepsy, especially with the advent of epilepsy protocol. The total percentage of MRI abnormalities increased after incorporating manual hippocampal volumetry.